Applying the Safe-And-Complete Framework to Practical Genome Assembly - Schmidt, Sebastian; Toivonen, Santeri; Medvedev, Paul; Tomescu, Alexandru I (Algorithms in bioinformatics : ... International Workshop, WABI ..., proceedings. WABI (Workshop), 2024)
Despite the long history of genome assembly research, there remains a large gap between the theoretical and practical work. There is practical software with little theoretical underpinning of accuracy on one hand and theoretical algorithms which have not been adopted in practice on the other. In this paper we attempt to bridge the gap between theory and practice by showing how the theoretical safe-and-complete framework can be integrated into existing assemblers in order to improve contiguity. The optimal algorithm in this framework, called the , has not been used in practice due to its complexity and its lack of robustness to real data. Instead, we pursue a simplified notion of omnitigs ( ), giving an efficient algorithm to compute them and demonstrating their safety under certain conditions. We modify two assemblers (wtdbg2 and Flye) by replacing their unitig algorithm with the simple omnitig algorithm. We test our modifications using real HiFi data from the and the genomes. Our modified algorithms lead to a substantial improvement in alignment-based contiguity, with negligible additional computational costs and either no or a small increase in the number of misassemblies.